Probiotics for the Treatment of Docetaxel-Related Weight Gain of Breast Cancer Patients—A Single-Center, Randomized, Double-Blind, and Placebo-Controlled Trial - Juan, Zhang; Qing, Zhang; Yongping, Liang; Qian, Liyuan; Wu, Wei; Wen, Yanguang; Tong, Jianbin; Ding, Boni (Frontiers in Nutrition, 2021)
Background: Docetaxel is an important chemotherapy-agent for breast cancer treatment. One of its side-effects is weight gain, which increases the all-cause mortality rate. Considering gut microbiota is one important factor for weight regulation, we hypothesized that probiotics could be potentially used to reduce the docetaxel-related weight gain in breast cancer patients. Methods: From 10/8/2018 to 10/17/2019, 100 breast cancer (Stage I-III) patients underwent four cycles of docetaxel-based chemotherapy were enrolled and randomly assigned to receive probiotics or placebo (three capsules, twice/day, for 84 days). Their body weight, body-fat percentage, fasting insulin, plasma glucose, lipids, metabolites, and fecal microbiome were measured one day before the chemotherapy and 21 days after the last cycle of chemotherapy. Results: Compared with the placebo group, the probiotic group showed significantly lower changes in body weight (Mean [SD] 0.77[2.58] vs. 2.70[3.08], P=0.03), body-fat percentage (Mean [SD] 0.04 [1.14] vs. 3.86 [11.09], P=0.02), and low density lipoprotein (LDL) (Mean [SD] -0.05[0.68] vs. 0.39 [0.58], P=0.002). Moreover, 5 of the 340 detected plasma metabolites showed significant differences between the two groups. The change of biliverdin dihydrochloride (B=-.724, P=0.02) was negatively correlated with weight gain. One strain of the phylum and three strains of the genus were detected to be significantly different between the two groups. Also, the changes of Bacteroides (B=-0.917, P<0.001) and Anaerostipes (B=-0.894, P<0.001) were negatively correlated with the change of LDL. Conclusions: Probiotics supplement during docetaxel-based chemotherapy for breast cancer treatment may help to minimize the changes in body weight, body-fat percentage, plasma LDL, together with the metabolic changes and gut dysbacteriosis. Trial Registration: 12/27/2017, Chinese Clinical Trial Registry (ChiCTR-INQ-17014181 [http://www.chictr.org.cn/showproj.aspx?proj=24294])